Foreign direct investment in Liberia 1945-1980 (Journal of the College of Basic Education, 2024)
During the period 1945-1980, Liberia had witnessed a qualitative economic boom as a result of the foreign direct investment policy. This policy is one of the most important outcomes of the open-door policy which adopted by President William Tubman, who, since assuming power, began opening the doors of the Liberian Republic to foreign investors to invest in its natural resources after the national financial and human capabilities were exhausted. The foreign direct investment policy has influenced all economic sectors in the country. It has transformed Liberia from a unilateral agricultural country to a multi-resource country that provided financial solvency. It had contributed to its economic, social and cultural development. As this policy lifted Liberia from the reality of devastation, ignorance and poverty, and made it the best country in West Africa economically. Thanks to this policy, Liberia has become the best economic country in West Africa and one of the most important economies in the world.